Antioxidant Activity and Phenolic Compounds of Ginger (Zingiber Officinale Rosc.) Determined By HPLC-MS/MS - Tohma, H.; Gülçin İ.; Bursal, Ercan; Gören A.C.; Alwasel S.H.; Köksal E. (Springer Verlag, 2017)
Oxidative stress related diseases often arise from over production of free radicals and reactive oxygen/nitrogen species. The prevention of these diseases could be possible with the use of natural antioxidant plants that could be promising as therapeutic candidates. Since antioxidant properties of a species could be stem from phenolic compounds, it is, therefore, important to evaluate antioxidant and total/individual phenolic and flavonoid content. For this purpose, we evaluated antioxidant properties of ginger (Zingiber officinale Rosc.) based on three parameters: the antioxidant capacity, total phenolic and flavonoid content as well as identification of phenolic acids of water extract (WEG) and ethanol extract (EEG) of ginger. For antioxidant capacity, we performed FRAP, CUPRAC assay, Fe2+ chelating ability, DPPH and DMPD radical scavenging activities. Also, total phenolic and flavonoid contents in both extracts were also measured via Folin Ciocalteu’s method. For identification of phenolic acids, HPLC-MS/MS method was performed. The results showed that EEG had generally better antioxidant activity than WEG in all assays. HPLC-MS/MS analysis showed that there are at least eight different phenolic acids found in ginger, among which pyrogallol p-hydroxybenzoic acid, ferulic acid and p-coumaric acid were more abundant in both extracts. This study clearly showed that ginger extracts demonstrated effective antioxidant properties and their consumption may reduce or delay the progression of diseases that oxidative stress take place due to lack of antioxidant supplementation. © 2016, Springer Science+Business Media New York.
Keywords: Antioxidant activity; Flavonoids; Ginger (Zingiber officinale Rosc.); HPLC-MS/MS; Phenols